2013
DOI: 10.2516/ogst/2012094
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of PredictedpKaValues for Some Amino-Acids, Dipeptides and Tripeptides, Using COSMO-RS, ChemAxon and ACD/Labs Methods

Abstract: Re´sume´-Comparaison des valeurs de pK a de quelques acides amine´s, dipeptides et tripeptides, pre´-dites en utilisant les me´thodes COSMO-RS, ChemAxon et ACD/Labs -Les valeurs de constantes d'acidite´(pK a ) jouent un roˆle tre`s important, en particulier dans l'industrie alimentaire. Les proprie´te´s chimiques des mole´cules de´pendent significativement de leurs e´tats d'ionisation. La plupart des mole´cules sont capables de gagner et/ou perdre un proton dans les solutions aqueuses. Ce transfert de proton a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, the results obtained using ACDLabs showed a slight sensitivity to the tautomeric species, as the p K a values determined for tautomers A and B differed by less than 1 p K a unit (Table ). These differences are surprising, as several studies have reported that these methods exhibit a close agreement in the p K a prediction of ionizable sites for a variety of compounds, leading to p K a estimates that accurately reproduce the experimental values (generally with mean average deviations <0.7 log units). However, these studies have often found discrepancies in the predicted p K a values that appear to be related to the presence of specific chemical features, which likely originate from the different natures of the formalisms used by these tools in the p K a prediction and the chemical diversity and structural complexity of the compounds included in the data sets. Overall, these data pose the question about the origin of the chemical factors that determine the experimental p K a of the two sets of tetrahydroazocino enamino ester derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…However, the results obtained using ACDLabs showed a slight sensitivity to the tautomeric species, as the p K a values determined for tautomers A and B differed by less than 1 p K a unit (Table ). These differences are surprising, as several studies have reported that these methods exhibit a close agreement in the p K a prediction of ionizable sites for a variety of compounds, leading to p K a estimates that accurately reproduce the experimental values (generally with mean average deviations <0.7 log units). However, these studies have often found discrepancies in the predicted p K a values that appear to be related to the presence of specific chemical features, which likely originate from the different natures of the formalisms used by these tools in the p K a prediction and the chemical diversity and structural complexity of the compounds included in the data sets. Overall, these data pose the question about the origin of the chemical factors that determine the experimental p K a of the two sets of tetrahydroazocino enamino ester derivatives.…”
Section: Resultsmentioning
confidence: 99%
“…1 . According to the ChemAxon method [ 25 – 27 ], the calculated p K a of three hydroxy groups are 7.4 (O6), 7.8 (O3), and 8.2 (O5). For that reason, the α-mangostin was considered as neutral molecule in the MD simulation (pH 7).…”
Section: Methodsmentioning
confidence: 99%
“…The COSMO‐RS algorithm allows the calculation of the chemical potential μi* of each compound i in a given solvent. The knowledge of μi* allows the calculation of a wide variety of thermodynamic properties, including the pK a of acids and bases, the Gibbs free energy of solvation and the activity coefficients . For a given compound i , the latter (γi(x)) is generally computed in molar scale and is calculated using Equation : γi(x)=expμi*μi*,0RT. …”
Section: Methodsmentioning
confidence: 99%